Comparative Study of Union Rate in Closed Humerus Shaft Fracture After Operative Fixation with Anteromedial Versus Anterolateral Surface Plating Using the Anterolateral Approach: A Randomized Controlled Study - Rattanakitkoson, Tana; Lothaisong, Narongrit; Ruangsillapanan, Naruepol (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Plate osteosynthesis is considered the gold standard for treating humeral shaft fractures, and orthopedic surgeons widely use the anterolateral approach with anterolateral surface placement. However, surgeons may have difficulties with the non-smooth surface and proximity to the radial nerve during their use. To address this challenge, we propose introducing the anterolateral approach with anteromedial surface placement. This study aimed to compare the outcomes between anteromedial and anterolateral surface plating using the anterolateral approach. Methods: This study included 74 patients who sustained a mid-shaft humerus fracture (AO 12) and underwent open reduction internal fixation between December 2020 and December 2022. Twelve patients were excluded based on the exclusion criteria. Among the remaining patients, 30 were randomized and allocated to surgery with anteromedial surface plating, while 32 patients were treated with anterolateral surface plating through an anterolateral approach. Postoperative clinical and radiographic results were recorded and analyzed. Results: The union rate, blood loss, operative time, and complications were not significantly different between the two groups. All the patients healed radiographically except for two in the anterolateral surface plating group, who required reoperation. Although anteroposterior alignment was significantly better in the anteromedial surface plating group, it was not clinically significant. Conclusions: Anteromedial plating demonstrated a commendable union rate, offered assured alignment, and presented itself as a secure option for addressing fractures of the humerus shaft.